Evaluasi User Experience EduSmart Menggunakan System Usability Scale (SUS) - Amanda Zulfi Kurnia Tsani (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Utilizing the System Usability Scale (SUS) method, the goal of this study is to understand the challenges faced by eduSMart users. Edusmart is an online learning platform. A survey consisting of several questions is conducted using the SUS method to improve the quality of work, efficiency, and ease of use. This study indicates that the user's SUS score indicates the use of tinggi. In the end, the platform needs to be improved to increase its capacity. The study's findings indicate how users should use the Edusmart platform and provide helpful advice for improving users' efficiency and enjoyment. The research findings can be used as a reference for future studies that assess the value of digital learning systems.